SISTEM INFORMASI PENGGAJIAN PANCAKEâS COMPANY - , SHINTA NOVITA L ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Pancakeâs Company is a restaurant that sells food such as pancake, waffle, poffertjes, and pasta. The salary processing in Pancakeâs Company uses a simple computer program. Based on the above condition, payroll information system of pancakeâs company is built to assist the processing information and data on pancakeâs company. This system can also facilitate the process of payroll employees at pancakeâs company. This information system is built using laravel framework, javascript, jQuery and MySQL database. This information system gives output attendance report and proofs of employee's payments in tables and can be printed.